Islamic Legal Perspectives on the Ethical Issues of Modern Biotechnology: A Case Study of Human Cloning and Genetic Engineering - Ali Reza Mahmudi (PT. Berkah Smart Academica, 2026)
This research is motivated by the legal ambiguities and ethical challenges arising from the rapid development of modern biotechnology, particularly human cloning and genetic engineering, which often outpace the speed of contemporary Islamic legal ijtihad. The objective of this study is to systematically synthesize Islamic legal perspectives on these ethical issues to provide guidelines for medical practitioners and policymakers. The methodology employed is a Systematic Literature Review (SLR) utilizing the PRISMA protocol, analyzing reputable academic literature from Scopus, Sinta, and Dimensions databases within the 2021-2025 period. The collected data reveal a clear legal fragmentation: reproductive cloning and germline genetic modification are widely rejected to protect the purity of lineage (Hifz al-Nasl), whereas therapeutic cloning and somatic cell genetic engineering are accepted as forms of medical benefit (Maslaha). The research conclusion emphasizes that Islamic law, through the Maqasid al-Shari'ah framework, is adaptive yet provides strict ethical boundaries to prevent dehumanization and biological exploitation. These findings offer a theoretical contribution to the development of interdisciplinary Islamic bioethics and a practical contribution in the form of policy recommendations for genetic research regulation in the Muslim world.